ANALISIS TITIK IMPAS DAN KEUNTUNGAN USAHATANI KARET DI DESA TALANG PERAPAT KECAMATAN SELUMA BARAT KABUPATEN SELUMA - Sugiarti, Sri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2005)
This research was aimed at estimacy to break even point, level of profit and barganing position on the marketing system, was conducted village talang Perapat, in the subdistrict of Seluma Barat Seluma district. Break even point analysis which describe the ratio between revenue and fixed cost and profit was used. At a selling price for structure rubber bat of beginning the seventh years Rp 1300, break even point 5,24 for Kg/Ha/ year were lower than average fild productivitas. In this situation, the level of profit and berganing position in structur rubber bath bath enough hing to be profitable.